(untitled) (International Journal of Food and Nutritional Sciences, 2024)
This paper proposes the integration of an SMS auto-reply feature into a Library Management System (LMS) to enhance user experience and streamline communication between the library and its patrons. The SMS auto-reply functionality aims to provide instant responses to queries, notifications, and updates initiated by library users via text messages. By leveraging this technology, libraries can ensure efficient communication, improve service accessibility, and ultimately elevate the overall user satisfaction.